The Varignano section (Trento Province, northern Italy): a chance to correlate shallow benthic zones and calcareous plankton zones near the Bartonian -Priabonian boundary - Papazzoni C. A.; Moretti A.; Fornaciari E.; Giusberti L.; LUCIANI, Valeria (Rendiconti online della Società Geologica Italiana, 2014)
The GSSP for the base of the Priabonian stage has not yet been defined, but a candidate section has been recently proposed near Alano di Piave (Veneto region, northern Italy), some 50 km far from the historical stage stratotype of Priabona. The Alano section, deposited in a bathyal setting, has been investigated for the calcareous nannoplankton, planktic foraminifera, as well as magnetostratigraphy. Unfortunately, at Alano di Piave there is no way to directly correlate with the larger foraminiferal shallow-water biozones, namely the Shallow Benthic Zones (SBZ). We present the results of the calcareous plankton and SBZ data from the Varignano section (Trento Province, northern Italy), that provides a unique chance for a direct correlation between shallow- and deep-water environments across the Bartonina-Priabonian boundary.